2007
DOI: 10.1590/s0100-40422007000500040
|View full text |Cite
|
Sign up to set email alerts
|

Síntese de amidas e sulfonamidas de beta-D-galactopiranosilamina e beta-lactosilamina e avaliação de suas interações com lectinas de Erythrina cristagalli e de Ricinus communis

Abstract: Recebido em 5/10/06; aceito em 18/12/06; publicado na web em 17/7/07 SYNTHESIS OF AMIDES AND SULFONAMIDES OF β-D-GALACTOPYRANOSYLAMINE AND β-LACTOSYLAMINE AND EVALUATION OF THEIR INTERACTIONS WITH THE LECTINS FROM Erythrina cristagalli AND Ricinus communis.We report herein the synthesis of some β-D-galactopyranosylamine and β-lactosylamine amides and sulfonamides. The interactions of these compounds with lectins from the seeds of Erythrina cristagalli (LEC) and Ricinus communis (RCA120) were evaluated in a hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…[1] In this report, we turned our attention to a panel of compounds with substitutions at the C6-positions in the Gal/Glc moieties of lactose and with different aromatic aglycons added to the lactoside. [24] The C6-positions can be substituted by O-…”
Section: Introductionmentioning
confidence: 99%
“…[1] In this report, we turned our attention to a panel of compounds with substitutions at the C6-positions in the Gal/Glc moieties of lactose and with different aromatic aglycons added to the lactoside. [24] The C6-positions can be substituted by O-…”
Section: Introductionmentioning
confidence: 99%
“…[19] Synthesis and characterization Synthesis of N-(b-d-glycosyl)methanesulfonamides: Per-Oacetylated b-d-glycosylamines were prepared by the reduction of per-O-acetylated b-d-glycosyl azides (1-8) using Pd/ C and hydrogen in dry CH 2 Cl 2 . Reaction of these glycosyl amines with methanesulfonyl chloride in the presence of triethylamine afforded the per-O-acetylated N-(b-d-glycosyl)methanesulfonamides (9)(10)(11)(12)(13)(14)(15)(16) in moderate to good yield with complete b-stereoselectivity (Scheme 1, Table 1). All the fully acetylated glycosyl methanesulfonamides (9)(10)(11)(12)(13)(14)(15)(16) were taken up for de-O-acetylation using BaA C H T U N G T R E N N U N G (OMe) 2 /MeOH at 0 8C.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of N-(b-d-glycopyranosyl)chloromethanesulfonamides: 2,3,4,6-Tetra-O-acetylb-d-glucopyranosylamine was allowed to react with chloromethanesulfonyl chloride under the same reaction conditions as used for the synthesis of fully acetylated glycosyl methanesulfonamides (9)(10)(11)(12)(13)(14)(15)(16), which resulted in only 30 % yield of the expected product. To improve the yield, the reaction was performed with different bases (N,N-diiosopropylethylamine (DIEA), 4-dimethyl-A C H T U N G T R E N N U N G aminopyridine (DMAP), and pyridine) and pyridine was found to be the best among all the bases chosen for the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[67][68] Similarly, Naringin is now recorded in the protocol for diagnosis and treatment of the novel coronavirus 69 . Besides, Das et al (2020) confirmed that rutin and hesperidin have anti-SARS-CoV-2 activity, under in vivo condition, by using molecular docking screening 70 . Further molecular docking approach will be recommended for the…”
Section: Lectins or Natural Products As Promising Therapy Against Covid -19mentioning
confidence: 99%